Dispersión Espacial: El Prerrequisito Esencial para el Muestreo. - Badii, M. H.; Guillen, A.; Cerna, E.; Landeros, J. (Revista Daena: International Journal of Good Conscience, 2011)
The relevance of spatial dispersion as an essential prerequisite for sampling is described. Different types of spatial dispersions are defined. Equations for estimating dispersion of Poisson, uniform and clumped types are provided. The existence and the estimation of common K is noted and assessed. Furthermore, the methods of estimation of following dispersion models and indices are given: Variance-mean ratio, Alexis index, Charlier index, models of David & Moore, Morisita, Taylor, Green, Cole, Lefkovitch, Lloyed, Iwao, and Pimbert & Jarry. Examples to use each of the above mentioned models and indices are provided. Criteria for choosing the best or perfect index or model are noted. Finally, the normal distribution and the necessity to transform data with different kinds of transformations are explained.